Pertumbuhan Tanaman Anggrek Dendrobium (Dendrobium sp.) pada Penambahan Berbagai Macam Pupuk Organik Cair - Sholiha, Nabila Fairuz; Setyaningrum, Tuti; Suwardi (Program Studi Agroteknologi INSTIPER, 2024)
Dendrobium orchids are popular plants with high economical value and high demands among the society. The poor quality of orchids is something that can be detected from the cultivation method, including its fertilization. This research aims to discover the impact of the AB mix combination and various types of POC, determine the best type of AB mix combination and POC, and examine the comparison of the AB mix fertilizer combination and types of POC with control fertilizer (AB mix). This research used a Completely Randomized Design (CRD) with a single factor consisting of 5 treatments + 1 control, which are 3 mL/L AB mix plus 150 mL/L POC rice washing excess water, coconut water, kepok banana peel, rabbit urine, cow urine. and control (AB mix). Observation parameters include plant height, stem diameter, number of leaves, number of tillers, length of tillers, and number of roots. Observations were analyzed using Variety Printing at the level of 5% and tested further with the Orthogonal Contrast Test and DMRT at the 5% level. From this research was obtained that the AB mix and POC combination had a significant effect on leaf number parameters. The combination of AB mix and POC rabbit urine was best for the growth of Dendrobium orchids in terms of plant height, number of leaves, leaf length, number of tillers, length of tillers and number of roots. The combination of AB mix and POC was better in terms of leaf number parameters than the control (AB mix)